SISTEM INFORMASI BIMBINGAN TUGAS AKHIR BERBASIS WEB PADA JURUSAN TEKNIK ELEKTRO POLITEKNIK SAINT PAUL - Murniyasih, Ery; Patandianan, Kartika Sari Dewi; Suryani, Luluk; Mandela, Wennie (LPPM Poltek ST Paul, 2025)
E-guidance services for student final project registration at Saint Paul Sorong Polytechnic are not yet available, therefore it is necessary to design and implement an information system that can provide convenience and manage the final project guidance process to make it easier to access information without having to meet face to face. The method used in this research is the SDLC (Systems Development Life Cycle) waterfall method where the waterfall model is a stage of several phases in sequence. This system was built using the PHP programming language assisted by the codeigniter framework and bootstrap. The results of blackbox testing show that the results of the existing features can run properly and normally in accordance with the system design. Web-based Final Project Guidance Information System is able to conduct final project guidance without having to hold meetings between lecturers and students so that it is more efficient. Students can do guidance and revision by sending documents on the features provided and lecturers respond to student documents and send revised documents on the upload feature. For each stage there is a history of guidance and a history of final project documents when the supervisor and students conduct guidance.